2001
DOI: 10.1088/0264-9381/18/5/101
|View full text |Cite
|
Sign up to set email alerts
|

BF gravity and the Immirzi parameter

Abstract: We propose a novel BF-type formulation of real four-dimensional gravity, which generalizes previous models. In particular, it allows for an arbitrary Immirzi parameter. We also construct the analogue of the Urbantke metric for this model. PACS: 04.60.DsReal general relativity can be formulated as a constrained first-order BF-type theory of the form [1] (for an earlier alternative approach, seewhere. . = 0, 1, 2, 3 are raised and lowered with the Minkowski metric η IJ ). G(B, φ, µ) denotes a constraint quadrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 27 publications
3
95
0
1
Order By: Relevance
“…This gives a direct evidence that the Immirzi parameter has no importance in our problem. 3 In [21] the Immirzi parameter was introduced in a different way. The difference comes from the Lagrange multiplier ϕ which was chosen to be a Lie-algebra valued field ϕ IJKL , whereas it is a density tensor ϕ µνρσ in our case.…”
Section: Notes On the Immirzi Parametermentioning
confidence: 99%
“…This gives a direct evidence that the Immirzi parameter has no importance in our problem. 3 In [21] the Immirzi parameter was introduced in a different way. The difference comes from the Lagrange multiplier ϕ which was chosen to be a Lie-algebra valued field ϕ IJKL , whereas it is a density tensor ϕ µνρσ in our case.…”
Section: Notes On the Immirzi Parametermentioning
confidence: 99%
“…Recently [75] it was also shown that the Barrett-Crane model arises quite naturally from a spin foam quantization of the most general BF-type action for gravity, proposed in [76], in the sense that a discretization of the constraints reducing BF theory to gravity in this new action shows their equivalence with the Barrett-Crane constraints on bivectors, and that a translation of them into conditions on the representations of the Lie algebra also gives the Barrett-Crane quantum constraints. This suggests the uniqueness of the Barrett-Crane constraints, in the sense that they arise whenever we express gravity in terms of 2-forms.…”
Section: Barrett-crane Model Plebanski Action Bf Theory and Generalmentioning
confidence: 99%
“…where the {j i } have integers and half-integers values, l p = (hG/c) 1/2 = 10 −33 cm is the Planck length and γ is a constant analogous to the Immirzi parameter [3]. The spectrum of the area operator is a very important result of loop quantum gravity.…”
mentioning
confidence: 99%